2018
DOI: 10.1016/j.apenergy.2018.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of hydrogen yield of a high-temperature electrolysis system with coordinated temperature and feed factors at various loading conditions: A model-based study

Abstract: High-temperature electrolysis (HTE) is a promising technology for achieving high-efficiency power-to-gas, which mitigates the renewable curtailment while promoting decarbonization by transforming wind or solar energy into fuels. Different from low-temperature electrolysis, a considerable amount of the input energy is consumed by auxiliary equipment in an HTE system for maintaining the temperature, so the studies on systematic energy description and parameter optimization of HTE are essentially required. A few … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 45 publications
(162 reference statements)
0
3
0
Order By: Relevance
“…The system electrical energy consumption, thermal energy consumption and efficiency in Scenario H-I and H-S are calculated as follows: P H = P ele + P + P Hc + P Ac [6] Q H = P e +P + P Sh + P Ah [7]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The system electrical energy consumption, thermal energy consumption and efficiency in Scenario H-I and H-S are calculated as follows: P H = P ele + P + P Hc + P Ac [6] Q H = P e +P + P Sh + P Ah [7]…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the constant steam utilization mode at low loads and the constant flow rate mode at high loads could achieve high efficiency over the whole load range. Xing et al (7) developed a concise analytical operation model to solve the maximum hydrogen production at a given system power by coordinating the temperature, feedstock flows, and electrolysis current. The proposed operation strategies extended the load range and improved the overall system efficiency, but this model did not consider the internal heat recovery of the system.…”
Section: Introductionmentioning
confidence: 99%
“…As the following sections introduce preheater thermal dynamics, stack electrical dynamics, and stack thermal dynamics, the electrode feed factors, gas-outlet partial pressure, average gas partial pressure, and gasoutlet flow rate expressions will be provided first. The following relations and equations are from [25,26].…”
Section: High-temperature Steam Electrolysis-solid-oxide Electrolysis...mentioning
confidence: 99%
“…Many researchers predict that the energy market will be based on hydrogen as a primary energy carrier in the future. Water electrolysis [3][4][5][6] is certainly the cleanest method for hydrogen production, and it is seen as the energy vector of a truly green and efficient energy system, assuming the electricity used in the process comes from renewable sources. Touted as the most favorable future scenarios are large-scale use of renewable energy [7] and/or biofuels [8].…”
Section: Introductionmentioning
confidence: 99%